Chlamydia trachomatis infection in female adolescents - Miranda, Angélica E.B.; Barcelos, Mara R.B.; Alves, Marta C.; Pedrosa, Denise M.R.; Vinhas, Solange A.; Warszawski, Josiane (Brazilian Journal of Sexually Transmitted Diseases, 2000)
Background: Toe female adolescents are a population group with an increased risk of STI, it is very imponant to follow their behavior faced to STJ/HIV/Aids. Objectives: validate a questionnaire to be applied in female adolescents and estimate the sample size necessary for doing a prevalence study of Chlamydia trachomatis infection in this population. Methods: Data were collected by a quantitative interview in a descriptive study of female adolescents ( 15 to 19 years old). A face-to-face questionnaire was applicd and it was collected a sample of urine to test CT using the LCX. AB BOTT laboratories. after signing an inform consent and parents authorization. Results: During tbe study period, 50 adolcscents were tested for Chlamydia. trachomatis, the prevalence rate was 8% (N=4). When it was considered 1be prevalence rate among those with sexually life, the rate was 11 .4%. Mean age was 17 .2 (SD 1.5) years; mean educalion was 8.3 (SD 2.9) ycars of schooling. Mean age of the first sexual intercourse was 15.4 (SD 1.6) years. Seventy percent of adolescents have alrcady had sexual intercourse. Conclusion: Data are in agreement with Lhe literature and it will bc uscd 10 estima te lhe frequcncy of Chlamydia infection and LO detennine risk factors associated. These data will be used to elaborate prevention aod education srrategies to improve the assistance to this population.